An experiment with barotropic quasi-geostrophic model for the Indian region - ASNANI, G. C. (MAUSAM, 1972)
In spite of the well known limitations of quasi-geostrophic models in the tropics, an experiment with quasi-geostrophic barotropic model was made for the region of India and neighbourhood for each day of the 2-month period from 25 October to 24 December 1966. 24-hour forecast was compared with the actual chart realised next day. R.M.S. error of the forecast is presented. The error in forecast for the region 10°N to 20°N was of the order of 20 gpm.